Persepsi Pengalaman Pertama Pada Pasien Gagal Ginjal Kronik Terhadap Hemodialisis Di Rumah Sakit Ananda Bekasi Jawa Barat - Yunidar Yunidar; Abdul Khamid; Achmad Fauzi (Malahayati Nursing Journal, 2022)
ABSTRACT The results of a systematic review and meta-analysis study conducted by Hill et al (2016) showed that 13.4% of the world's population suffers from chronic kidney failure. Several occurrences of comorbidities after experiencing kidney disorders in chronic kidney failure patients undergoing hemodialysis cannot be avoided, where these complications can cause discomfort, increase stress anxiety and have a negative impact on the quality of life of patients including family dynamics. The purpose of this study was to explore the perception of the first experience of chronic kidney failure patients on hemodialysis at Ananda Hospital Bekasi, West Java. The sampling technique used was purposive sampling. The number of informants in this study was four patients with chronic kidney failure and four from families of patients with chronic kidney failure. Data were collected by in-depth interviews with four participants and four people from their families. In patients with CRF, it is carried out 1 or 2 times a week and lasts for at least 3 months continuously. Some of the effects or risks of hemodialysis must be faced by CKD patients considering this action is one of the actions that are also beneficial in maintaining their survival. The decision of a patient with chronic renal failure to undergo hemodialysis is when a patient with chronic kidney failure performs dialysis for the first time, which is not inconceivable at all. Keywords: Perception, Hemodialysis, Chronic Renal Failure ABSTRAK Hasil studi systematic review dan meta analisys yang dilakukan oleh Hill dkk (2016) menunjukkan 13,4% penduduk dunia menderita gagal ginjal kronis. Beberapa kejadian adanya penyakit  penyerta setelah mengalami gangguan ginjal pada pasien gagal ginjal kronis yang menjalani hemodialisa tidak dapat dihindari, dimana komplikasi tersebut dapat menimbulkan ketidaknyamanan, meningkatkan stress kecemasan dan berdampak buruk pada kualitas hidup pasien termasuk didalamnya dinamika keluarga. Tujuan penelitian ini untuk mengeksplorasi persepsi pengalaman pertama pada pasien gagal ginjal kronik terhadap Hemodialisis di Rumah Sakit Ananda Bekasi Jawa Barat. Teknik pengambilan sampel menggunakan purposive sampling. Jumlah informan dalam penelitian ini ada empat pasien gagal ginjal kronik dan empat dari keluarga pasien gagal ginjal kronik. Pengumpulan data dilakukan dengan wawancara mendalam pada empat orang partisipan dan empat orang dari keluarga. Pada pasien GKK dilakukan 1 atau 2 kali seminggu dan sekurang-kurangnya berlangsung selama 3 bulan secara berkelanjutan. Beberapa dampak atau resiko hemodialisa harus dihadapi oleh pasien GGK mengingat tindakan ini merupakan salah satu tindakan yang juga bermanfaat dalam mempertahankan kelangsungan hidupnya. Keputusan Pasien gagal ginjal kronik untuk dilakukan hemodalisis adalah saat pasien gagal ginjal kronik  untuk pertama kalinya melakukan cuci darah yang tidak kebayangan sama sekali. Kata Kunci: Persepsi, Hemodialisis, Gagal Ginjal Kronik